Effects of physical activity on mobile phone addiction among university students: the mediating roles of self-control and resilience - Wang, Fang (Frontiers in Psychology, 2025)
BackgroundIn recent years, mobile phone addiction (MPA) has emerged as a significant public health concern, particularly among university students. Physical activity (PA) is believed to exert a beneficial influence on MPA within this demographic. However, the extent to which this influence is moderated by other factors remains uncertain. Evidence points to self-control and resilience as potential mediators that may partially account for the positive impact of PA on MPA. Accordingly, this study seeks to investigate the effect of PA on MPA and the mediating role of self-control and resilience in this relationship through a chain-mediated model.MethodsThe study involved 413 Chinese university students (208 males, mean age 20.59 ± 1.17 years), who completed the PA Rating Scale (PARS-3), the Connor-Davidson Resilience Scale (CD-RISC), the Self-Control Scale (SCS), the Mobile Phone Addiction Index (MPAI), along with other psychosocial assessments. Pearson’s correlation was employed to analyze the relationships between variables, while mediation models were examined using SPSS PROCESS and bootstrapped regression analysis.ResultsPA demonstrated a significant negative correlation with mobile phone addiction behaviors (β = −0.22, p < 0.01). Self-control and resilience moderated the relationship between PA and mobile phone addiction. Notably, PA influenced mobile phone addiction through the chain-mediated effects of self-control and resilience.ConclusionCollege students can alleviate MPA issues by consistently engaging in healthy PA, which is essential for enhancing self-control and bolstering resilience.